Suspected neonatal isoerythrolysis with concurrent Actinomyces hyovaginalis in a foal - Lim, Eric Teik Chung; Adamu, Lawan; Abdullah, Faez Firdaus Jesse; Wakil, Ya Kaka; Solomon, Esther Mshelia; Turaki, Usman Aliyu (Network for the Veterinarians of Bangladesh, 2018)
Objectives: This case report aimed at diagnosing and instituting timely intervention to avert Neonatal Isoerythrolysis with concurrent infections in foals. Material and Methods: Baby Dokki is a one day old, filly, foal, pony cross, weighing about 20kg. She is managed in a stable with its dam. Baby Dokki was found dead a day after her birth. Post mortem examination revealed a generalized jaundice in the mucous membrane, muscles and aorta. Besides that, the synovial fluids were also thicken and yellowish. As well, the large intestine contains very hard greenish fecal material obstructing the rectum. Softer yellowish fecal material was found to be impacted dorsal to the hard fecal material. Results: Furthermore, the bacteriology result divulged the presence of Actinomyces hyovaginalis. In addition, blood was also collected from the mare and the stallion to check for blood compatibility. Conclusion: Thus, the case was diagnosed as suspected neonatal isoerythrolysis with concurrent Actinomyces hyovaginalis infection.